Legal Requirements for the Protection of Layout Designs of Integrated Circuits - Aldhoori, Aisha; Alkaswani, Nazal (Journal of Legal Sciences, 2026)
The accelerating pace of modern technological development poses an ongoing challenge for legislators in safeguarding the rights arising from technical innovations. Among the most prominent of these innovations are the layout designs of integrated circuits, which constitute a fundamental component in the production of sophisticated electronic devices. The significance of protecting such designs lies in their origin as outcomes of intricate intellectual efforts and high-cost engineering processes, rendering any infringement a serious breach of sensitive intellectual property rights. Federal Law No. 11 of 2021 in the United Arab Emirates provides a coherent and structured legal framework for the protection of these designs by defining the procedures for registration, the duration of protection, the substantive conditions required to obtain legal rights, and the penalties applicable in cases of infringement. The law also demonstrates a clear commitment to balancing the encouragement of innovation with the safeguarding of third-party rights, through its adherence to internationally recognized standards. This legal structure is intended to foster a secure environment conducive to investment in advanced technologies, thereby enhancing the UAE’s position in the global knowledge-based economy. Nonetheless, there remains a pressing need for the periodic revision of relevant legislation to ensure its responsiveness to the evolving technological landscape and the practical challenges associated with its implementation in this critical field.